Strategi Rekrutmen dan Seleksi Guru di Lembaga Pendidikan Islam: Pendekatan Analisis Pekerjaan dan Nilai-Nilai Islami - Ansori, Ansori; Yusup, Muhammad; Riyadi, Sugeng; Ritonga, Nurhayani (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Job analysis is a fundamental component of human resource management, particularly in the recruitment and selection processes within Islamic educational institutions. It functions as a systematic approach to identifying and defining the duties, responsibilities, qualifications, and competencies required for specific positions, thereby ensuring alignment between institutional needs and individual capabilities. In the context of Islamic education, job analysis extends beyond technical and professional competencies to include moral integrity, spiritual commitment, and noble character as core requirements for educators. Clear and well-structured job descriptions and job specifications serve as essential instruments for attracting candidates who are not only competent in their fields but also committed to upholding Islamic values. Furthermore, the recruitment and selection process should be implemented objectively and transparently through appropriate methods such as competency-based testing, structured interviews, assessment centers, and fit and proper tests. These techniques are necessary to evaluate both professional qualifications and the suitability of candidates’ values with the vision and mission of Islamic educational institutions. In addition, the application of Islamic ethical principles—such as justice, trustworthiness, professionalism, transparency, and the rejection of nepotism—plays a crucial role in creating a fair, accountable, and credible recruitment system. Comprehensive job analysis combined with value-based selection processes is therefore strategic in producing educators who are professionally competent and morally exemplary, ultimately contributing to the enhancement of quality, integrity, and public trust in Islamic educational institutions.